Tinjauan Prinsip Kepentingan Terbaik bagi Anak dan Maqashid Syariah dalam Dispensasi Kawin: Studi Putusan Pengadilan Agama Nabire Nomor 41/Pdt.P/2019/PA.Nbr - Farhan Yasin (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study analyzes the decision of the Nabire Religious Court Number 41/Pdt.P/2019/PA.Nbr from the perspectives of the best interests of the child principle and maqashid sharia. It is a normative legal study employing case and conceptual approaches. The research uses primary legal material in the form of the court decision and secondary legal materials, which are analyzed descriptively and qualitatively. The findings show that the judges’ reasoning in granting the marriage dispensation was mainly directed toward resolving the immediate consequences of an out of wedlock pregnancy and protecting the fetus. The study concludes that the decision has not fully reflected the best interests of the child principle nor the objectives of maqashid sharia, as it overlooked educational, health, psychological and future welfare considerations. This study contributes to strengthening child centered and maqashid based judicial reasoning in marriage dispensation cases.